Efek Diuresis Ekstrak Propolis pada Tikus Putih Jantan (Rattus Norvegicus) - Fadityo, .; Doewes, Muchsin; ., Kisrini (Nexus Kedokteran Translasional, 2012)
Background:Diuretics are medicine that increase the amount ofÂ  urine volume. Propolis has 150 compounds that have biological activities, one of the is flavonoid. Flavonoid known to has diuretic effect. Methods:The research is a laboratory experimental analytic study using randomized controlled trial done at Laboratory of Setia Budi University Surakarta in June 2012. The research subject is a number of 35 male white rats of Wistar strain. They were divided into five treatment groups, each group consists of seven rats. Simple random sampling is used for sampling technique. Before the treatment,Â  rats were adapted for 7 days and fasted for 48 hours but still provided with drinking water. Propolis extract was given orally. Group I was given aquadest 2.5 ml as negative control, group II was given hydrochlorothiazide 0.3 mg/2.5 ml as positive control, group III was given propolis extract at dose 30 mg/2.5 ml as dose I, group IV was given propolis extract at dose 60 mg/2.5 ml as dose II, and group V was given propolis extract at dose 120 mg/2.5 ml as dose III. Rats urine volume was measured every 6 hours for 24 hours. Results:Result of statistic calculation using Anova test with p < 0.05 shows that there is significant difference in total rats urine volume between group I, II, III, IV, and V. The Post-Hoc test result between group I compared with the others group was significant difference.Group II has the largest urine volume from all groups. Group III has the largest urine volume among the groups that given propolis extract. Group IV has larger urine volume than group V and group V has the least urin volume among the groups that given propolis extract. Conclusions:Through observing amount of urine volume and statistic calculation, it can be concluded that propolis extract has diuretic effect in the male white rats.The increase of propolis extract dose cause the decrease of urine volume. Keywords:Propolis extract, hidroclorotiazid, diuretic